Kultywowanie szacunku dla samego siebie - Grom, Bernhard (Horyzonty Wychowania, 2017)
In the past three decades psychology has been showing thesignificance of a positive sense of one’s own value for life satisfactionamong children, youth and adults and has worked outmethods helpful in becoming aware and realizing one’s ownneeds and rights. The aim is not to support egocentric or narcissisticattitudes, but to prevent a feeling of dejection and lack ofhappiness. What is the meaning of such cultivation of the senseof one’s own value? According to Kant’s mind ethics, man isobliged to provide himself with „moral recognition” and to guardhis dignity. Theological ethics and spirituality supplement thisone-sidedly moral justification of cultivating respect for yourselfand shows that man should respect himself in his whole as„likeness” of the Creator and His „friend”, loved by the Son ofGod „to the uttermost”, for whom He laid down His life (John13, 1; 15, 13-15). Together with this God he should love himselfand avoid any self-depreciation. Christian spirituality may makethis message more effective if it listens to what psychology saysabout the threats to the sense of one’s own value.